Myeloid cells require gp130 signaling for protective anti‐inflammatory functions during sepsis. Issue 5 (6th February 2019) - Sackett, Sara Dutton; Otto, Tobias; Mohs, Antje; Sander, Leif E.; Strauch, Sonja; Streetz, Konrad L.; Kroy, Daniela C.; Trautwein, Christian
ABSTRACT: Sepsis represents a major health problem worldwide because of high mortality rates and cost‐intensive therapy. Immunomodulatory strategies as a means of controlling overshooting inflammatory responses during sepsis have thus far not been effective, and there is a general paucity of new therapies. Regulatory immune cells have been shown to play important roles in limiting systemic inflammation. However, the signals inducing a regulatory phenotype in myeloid cells during infection are unknown. Here, we report that myeloid cell–intrinsic glycoprotein 130 (gp130) signals constitute a critical element for immune homeostasis during polymicrobial sepsis. We identify an essential role for gp130 signaling in myeloid cells during M2 macrophage polarization in vitro and in vivo . Myeloid cell–specific deletion of gp130 signaling leads to a defective M2 macrophage polarization followed by exacerbated inflammatory responses and increased mortality during sepsis. These data provide new insights into the molecular basis of M1 and M2 phenotypic dichotomy and identify gp130 as a key regulator of immune homeostasis during sepsis. Our study highlights the Janus‐faced role of IL‐6 family cytokines during inflammation, which may explain the failure of IL‐6–targeted anti‐inflammatory approaches in the treatment of sepsis.—Sackett, S. D., Otto, T., Mohs, A., Sander, L. E., Strauch, S., Streetz, K. L., Kroy, D. C., Trautwein, C. Myeloid cells require gp130 signaling for protective antiinflammatory functions during sepsis. FASEB J. 33, 6035–6044 (2019). www.fasebj.org